Genesis of Sulfur Deposits in Lechuguilla Cave, Carlsbad Caverns National Park, New Mexico - C. S. Spirakis; K. I. Cunningham (Society for Mining, Metallurgy & Exploration, 1992)
Two types of native sulfur deposits have been found in Lechuguilla Cave: thin late-stage crusts and massive early- formed deposits. Most, if not all, of the crusts appear to have formed by remobilization of native sulfur contained within gypsum and sulfur masses. The process is occurring today and is slowly converting the sulfur to gypsum. The absence of primary gypsum or reductants in the cave indicates that the early-formed massive sulfur deposits did not form by in-place reduction of sulfate, which is the process that formed the commercial sulfur deposits in the Delaware basin. Instead, it appears that H2S dissolved in basinal brines was oxidized by oxygen in near-surface ground waters in the cave. Fluid- inclusion data, which suggest the presence of both fresh water and saline water as the sulfur formed, support this interpretation. Although individual sulfur deposits in Lechuguilla Cave are no more than several tens of metric tons, the abundance of secondary gypsum (as much as 10 meters thick) indicates that native sulfur may once have been much more extensive.